Electrodynamic characteristics of high order modes in biperiodic accelerating structure - Kaminsky, V.I.; Kosarev, A.A.; Sobenin, N.P.; Sulimov, A.A. (Вопросы атомной науки и техники, 2001)
The influence of coupling slot number and geometric sizes, and diaphragm thickness between cells on electrodynamic characteristics (EDC) of biperiodic accelerating structure (BAS) on main and dipole oscillation modes are investigated. The research is executed with the help of solution of a three-dimensional problem by computing methods. The adjustment possibilities of dipole mode frequency to keep out from the condition of multiplicity to frequency of working mode of oscillation were shown.